2012
DOI: 10.1111/j.1365-2796.2012.02535.x
|View full text |Cite
|
Sign up to set email alerts
|

Clopidogrel and the risk of osteoporotic fractures: a nationwide cohort study

Abstract: Abstract. Jørgensen NR, Grove EL, Schwarz P, Vestergaard P (Research Center for Aging and Osteoporosis, Copenhagen University Hospital Glostrup; Aarhus University Hospital, Skejby; University of Copenhagen, Copenhagen; The Osteoporosis Clinic, Aarhus University Hospital, Denmark). Clopidogrel and the risk of osteoporotic fractures: a nationwide cohort study. J Intern Med 2012; 272: 385-393.Objectives: The P2Y 12 inhibitor clopidogrel inhibits platelet aggregation and is used in the treatment and prevention of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…A cohort study including all patients treated with clopidogrel in Denmark during a 10-year period (n ¼ 77,503) and an age-and gender-matched control group (n ¼ 232,510) showed that patients on clopidogreltreatment had an increased risk of fracture of approximately 50% compared to the control group. (54) This study focused on the effects of clopidogrel, which is the major compound currently in therapeutic use. However, other P2Y 12 receptor antagonists (Prasugrel, Elinogrel, and Tricagrel) are now becoming available therapeutically; whether these drugs effect bone cell function in vitro and in vivo is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A cohort study including all patients treated with clopidogrel in Denmark during a 10-year period (n ¼ 77,503) and an age-and gender-matched control group (n ¼ 232,510) showed that patients on clopidogreltreatment had an increased risk of fracture of approximately 50% compared to the control group. (54) This study focused on the effects of clopidogrel, which is the major compound currently in therapeutic use. However, other P2Y 12 receptor antagonists (Prasugrel, Elinogrel, and Tricagrel) are now becoming available therapeutically; whether these drugs effect bone cell function in vitro and in vivo is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“… 4 As patients with cardiac comorbidities requiring these drugs are often similarly at risk for osteoporosis and thus for fragility fractures, this population presents a unique dilemma for orthopedic surgeons who perform emergent, urgent, as well as elective operations on these patients. 5 Additionally, a nationwide cohort study published in 2012 by Jørgensen et al concluded clopidogrel taken by itself in the recommended dose range is associated with a risk of fractures, although the in vivo effects of antiplatelet drugs on bone metabolism are uncertain. 5 …”
Section: Introductionmentioning
confidence: 99%
“… 5 Additionally, a nationwide cohort study published in 2012 by Jørgensen et al concluded clopidogrel taken by itself in the recommended dose range is associated with a risk of fractures, although the in vivo effects of antiplatelet drugs on bone metabolism are uncertain. 5 …”
Section: Introductionmentioning
confidence: 99%
“…In this study, individuals who took clopidogrel for more than one year had an increased risk of fracture while patients who took the drug for less than one year had a lower risk of developing a fracture compared to those who had never taken the drug (Jorgensen et al, 2012a). The reason for the time-dependent differences in results is not yet known, but this large study demonstrates that P2Y 12 is likely an important mediator of normal bone maintenance.…”
Section: P2 Receptors and Bonementioning
confidence: 89%